Inappropriate secretion of antidiuretic hormone in infants with respiratory infections. Issue 5 (May 1981) - Rivers, R P; Forsling, M L; Olver, R P
Abstract : Four infants in whom excessive secretion of antidiuretic hormone was associated with pulmonary infections are reported. Severe hyponatraemia was noted in 3 of them; in the fourth, fluid restriction may have prevented this complication.